2007
DOI: 10.1159/000100807
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Protoporphyrin/Heme in Large-for-Gestation Newborns

Abstract: Background: Zinc protoporphyrin/heme (ZnPP/H) ratios are indicators of incomplete erythrocyte iron delivery. ZnPP/H is more sensitive than measures of iron stores, such as plasma ferritin, in identifying early pre-anemic iron-deficient erythropoiesis. Cord ZnPP/H ratios are elevated in conditions associated with fetal hypoxia, such as diabetes mellitus during pregnancy. In chronic fetal hypoxemia, erythrocyte and hemoglobin syntheses are accelerated and iron is incorporated into erythrocytes. Cord ZnPP/H ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…35, 36 Although the occurrence of LGA newborns was more common after pregnancies with maternal obesity, 1 being LGA was not the sole basis for poorer cord iron status. 30 Rather, we confirmed that fetal overgrowth compounded the effect of maternal diabetes on newborn iron status, supporting previous work. 24, 30, 32, 37 The effect of obesity on ZnPP/H, RE-ZnPP/H and serum ferritin was not lost in multivariate analysis, supporting that maternal obesity was independent of diabetes or newborn size in determining biochemical iron status.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…35, 36 Although the occurrence of LGA newborns was more common after pregnancies with maternal obesity, 1 being LGA was not the sole basis for poorer cord iron status. 30 Rather, we confirmed that fetal overgrowth compounded the effect of maternal diabetes on newborn iron status, supporting previous work. 24, 30, 32, 37 The effect of obesity on ZnPP/H, RE-ZnPP/H and serum ferritin was not lost in multivariate analysis, supporting that maternal obesity was independent of diabetes or newborn size in determining biochemical iron status.…”
Section: Discussionsupporting
confidence: 91%
“…30 During accelerated fetal erythropoiesis, transport of available fetal iron is prioritized to the erythrocytes at the expense of other tissues. 31 A direct relationship between BMI and the ratio of Hb/total body iron supports this view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide a reference comparison, we generated cord blood laboratory data from a recent representative population of 188 healthy newborns born at ≥35 weeks of gestation, delivered from mothers of all ethnic backgrounds at Meriter Hospital without other known risk factors for IDA. 6,10,11 …”
Section: Methodsmentioning
confidence: 99%
“…Birth weight was z -scored for gestational age, and used to ascertain whether the neonate exceeded the criterion for LGA as >2 or SGA as <−2. 10,12 One-way and multiple ANOVA with Fisher post hoc testing were used to compare differences between the groups and the Pearson test was used to evaluate correlations between outcome measures. Chi square analysis was used for nominal demographic variables.…”
Section: Methodsmentioning
confidence: 99%